(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
This investigation aimed to assess the influence of soil-applied vermicompost, nitrogen and zinc on the vegetative growth parameters, yield, and mineral nutrient concentration of the fruits of okra (Abelmoschus esculentus L. Moench). The experiment was laid out in a Completely Randomized Design followed by three replications. Data were subjected to analysis of variance and mean values were compared using Tukey’s Range Test at p ≤ 0.05. Variation in mean values was compared among eight treatments: control (T1), 6 ton ha-1 vermicompost (T2), 60 kg ha-1 N (T3), 2 kg ha-1 Zn (T4), 6 ton ha-1 vermicompost + 60 kg ha-1 N (T5), 60 kg ha-1 N + 2 kg ha-1 Zn (T6), 6 ton ha-1 vermicompost + 2 kg ha-1 Zn (T7), and 6 ton ha-1 vermicompost + 60 kg ha-1 N + 2 kg ha-1 Zn (T8). The maximum growth performance and yield contributing properties of okra, viz. plant height (56 cm), leaf number (11 plant-1), leaf area (14.5 cm2), stem girth (3.5 cm), branch number (8 plant-1), and fruit number (6.50 plant-1), fruit diameter (5.50 cm), fruit length (13.50 cm), and weight of fresh (64.29 g) and dry plant materials (14.56 g), were found in T5. The control T1 performance showed reducing trends compared to other treatments. Although there was no significant difference with the application of vermicompost 6 t ha-1 + N 60 kg ha-1 + Zn 2 kg ha-1 (T8), the treated pot in vermicompost with 6 t ha-1 + N 60 kg ha-1 (T5) showed the best achievements of macro elements N (0.008%), P (6.70 ppm), K (0.08 cmol/kg), and S (18.22 ppm) of post-harvest soil compared to the control T1. Mineral nutrients of fruits N-1.64%, P-0.27%, K-0.30%, S-0.10%, and Fe-0.02% and protein content 10.23% were found to be highest in the identical T5 where Zn content was highest (0.28%) in T8. This study showed that the treatment of vermicompost with 6 t ha-1 + N 60 kg ha-1 (T5) contained and released quality nutrients is recommended for its overall best growth performance for okra. J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 101-108